Modeling and Simulation of Magnetizing Inrush Current in A Single-Phase Transformer - Altun, Huseyin; Sunter, Sedat; Aydogmus, Omur (Ieee, 2019)
In this paper, a transformer model has been developed. The model is based on the equivalent electrical circuit used in transient simulation studies which considers the non-linearity of the iron core. The non-linear ferromagnetic behavior of the iron core was obtained by using the Jiles-Atherton hysteresis model. The magnetizing inrush current of a core type single-phase transformer was analyzed under four different energization conditions. The primary winding of the transformer was connected to the supply at various instants while there was either some level of remanent flux or no remanent flux in the iron core. Corresponding simulation results are presented and discussed.
4th International Conference on Power Electronics and their Applications (ICPEA) -- SEP 25-27, 2019 -- Elazig, TURKEY
Keywords: transformer modeling; magnetizing inrush current; Jiles-Atherton Hysteresis Model